The climate organizational and its influence in the performance of workers at company GSH S.A. - Carhuayal Huaranga, Olga Liz (2020)
Studies on organizational climate began to have relevance because of the formation of a group as an organization, attributing external and internal causes on the one hand with negative and positive effects on the other hand, the latter being an essential element for the worker to feel motivated and supported by the people around him, resulting in higher performance, profitability and productivity in the members that make up the organization. This construct has been directly related to group performance, since both concepts are controlled by the worker and driven, positively or negatively, by managers, senior staff and the culture of the organization. However, in the context of family businesses these concepts are unknown or simply give the appearance of being accepted by the workers, in such a way that the owner or manager of the company does not care about motivating or encouraging the staff and therefore provide a better work environment within your company.